Evaluation of Strength Deterioration Factor on Blended Concrete Exposed to Magnesium Sulphate Solution. Issue 1 (November 2020) - Jena, Trilochan; Chandra Panda, Kishor; Panda, Chittaranjan
Abstract: This paper reports the combined effects of industrial waste as fly ash (FA) and agro-waste such as silpozz on the compressive strength and strength deterioration factor (SDF) of blended cement concrete exposed to 5% and 10% MgSO4 solution and normal water. Silpozzis manufactured by burning of agro-waste rice husk in designed furnace in between 600° to 700°C which is one of the main agriculture.al residues obtained from the outer covering of rice grains during the milling process. There are four mix series taken with control mix. The control mix made 0% replacement of FA and silpozz with Ordinary Portland Cement (OPC). The first mix series made 0% FA and 10-30% replacement of silpozz with OPC. The second mix series made with 10% FA and 10-40% replacement of silpozz with OPC. The third mix series made 20% FA and 10-30% replacement of silpozz with OPC and the fourth mix series made 30% FA and 10-20% silpozz replaced with OPC. The samples (cubes) are prepared and cured in normal water and 5% and 10% MgSO4 solution for 7, 28 and 90 days. The studied parameters are compressive strength and strength deterioration factor (SDF) for 7, 28 and 90 days. The regression equations and value of correlation coefficient R2 between compressive strength and partial replacement of silpozz is obtained and revealed from these results that value of correlation coefficient is varied from 0.9602 to 1.